Batimetria e aspectos morfodinâmicos de canais de maré da Costa Leste da Ilha do Marajó (PARÁ) - NASCIMENTO, Inaê de Brito Albuquerque (2019)
Coastal zone is a very unstable environment, which is constantly reworked by erosive and depositional processes, mainly by action of waves, tides and coastal currents, what makes the monitoring of these environments critical. Among the different coastal environments, we can mention the estuaries and tidal flats. Tidal channels are important for the development of tidal flats and mangroves, and for drainage and distribution of nutrients and sediment. This environments are subject to external modifications, for example, increasing the relative sea level and anthropogenic activities, in this way understanding the processes the govern the development and evolution of tidal channes is essential. It was verified the bathymetry, the variation of tidal channel between April/May, August and December 2010, water turbidity and it was observed bed forms in Limão and Jubim tidal channels in Salvaterra, Uruci e Andiroba (Pesqueiro) tidal channels in Soure, east coast of Marajó Island, State of Pará. Limão, Jubim, Uruci e Andiroba tidal channels are shallow (maximum depth of approximately 5 m) with the presence of numerous sandbanks, under a mesotidal regime (ranging from 3.28 m in Uruci tidal channel and 2.58 m in Limão and Jubim tidal channels) associated to extensive wetlands, located in a high hydrodynamic region, with a predominance of sandy sediments and presenting a variety of energy flow, which is indicated by the variety of bed forms observed over the intertidal flats associated to channels. Water turbidity presented its peak between the beginning and middle of the ebb tide, and lowest during high tide, identifying the tidal channels as exporters of suspended particulate matter. Present study was a previous characterization of Limão, Jubim, Uruci and Andiroba tidal channels’ morphodynamics, tidal channels located in the east coast of Marajó Island.